TEACHING STUDENTS’ VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE - Risma Gayanti; Intan Satriani (IKIP Siliwangi, 2020)
Learning English during this time globalization is exceptionally critical. People aspire to speak fluent in English. This proves that the presence of English during this time globalization is exceptionally imperative and considering that English is an international language. However, many Indonesians people cannot master vocabularies well, due to lack of understanding when studying in the class. The population of students were 130 within the eighth grade, but researcher using 1 class, there are 35 students within the class for this study. Thereby, the aims of this research is to find the vocabulary improvement of Total Physical Response (TPR). The researcher used qualitative method. Interview and test used as instrument of this research.The result showed that students more understand and truly remember of recent vocabularies when using Total Physical response (TPR) as a way. It can be concluded that students can improved their vocabularies well through TPR. Keywords: Vocabulary, Total Physical Response